Basic education improvement: A case of two High Schools in Tanahu, Nepal. - Poudel, Durga D.; Aryal, Arjun; Masuno, Naomi; Paterson, Mary; Yount, Christel; Ching, Randall; Brahmst, Joy Robin; England, Kara; McRoberts, Jonathan; Chamberlain, Andy; et al. (Scientific Journal of Bielsko-Biala School of Finance and Law, 2023)
Improving basic education in High School is critical for developing skilled manpower. Two High Schools, Shree Jana Jukta Shai Secondary School and Shree Udaya Secondary School, in Tanahu, Nepal, have recently started their intermediate and technical education programs in veterinary science, civil engineering, and agriculture. This study was done to better understand basic education improvement opportunities and challenges in these two High Schools. We assessed needs and identified academic activities for basic education improvement. Accordingly, we developed basic science and engineering laboratories and E-Learning facilities in these two High Schools, conducted a two-day teacher’s trainingand classroom teaching demonstration, and organized a three day adult science literacy training in the communities. Topicscovered in the teacher’s training and adult science literacy events primarily included related to agriculture, environment, and climate change. The effectiveness of the basic education improvement program was assessed through observation, key informant surveys, group discussion, and feedback from teachers, students, and local communities. The program successfully developed basic science education in these two schools.